PENGARUH MOTIVASI KERJA DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL PADA SEKOLAH MENENGAH KEJURUAN DI LINGKUNGAN YAYASAN PUSAT PENGEMBANGAN ILMU DAN TEKNOLOGI TEXMACO - Subakin, 1352020005 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the Effect of Work Motivation and Emotional Intelligence on teachersâ Performance Mediated by the Organizational Commitment In Vocational High School in Texmaco Foundation of Science and Technology Development Center. This study is an explanatory research which is aimed at explaining the influence of variables of the research and testing the hypothyses of the study formulated. In this study, the population is all Texmaco vocational high school teachers in the Texmaco Foundation of Science and Technology Development Center. ,while the sample used in this study is 129 people as the respondents by using proporsionate accidental sampling technique. The criteria of the respondents are from the full-time and part-time teachers of Texmaco Vocational High School Semarang. The measurement was done by using a Likert scale with seven (7) alternative answers. The test instrument used in this study was the validity and reliability, normality test, multicollinearity and heteroscedasticity. While the test model used is the coefficient of determination and F test. In addition, the hypothesis test used the regression analysis. Based on the results of the study it can be summarized as follows: the motivation has the positive and significant impact to the Organizational Commitment, the Emotional Intelligence does not affect to the Organizational Commitment, the Work Motivation also has the positive and significant impact on the teacher performance, Emotional intelligence does not affect the Teacher Performance, the Organizational Commitment affects the Teacher Performance and it does not mediate the effect of motivation and emotional intelligence to the teachers performance. Keywords: Work Motivation, Emotional Intelligence, Organizational Commitment, teacherâs performance